(untitled) (Medico Legal Update, 2020)
Low fish consumption in some parts of Indonesia is caused by the high price of several types of fish. Its include types of fish that have a low social value in the community so it is less desirable although their value of nutrients is very good. Anchovy is actually the best source of calcium and protein. Calcium in white anchovy (Stolephorus sp) is very stable resistant and not easily soluble in water. White anchovies (Stolephorus sp) are excellent as a source of calcium and protein in children who are in their infancy, expectant mothers, nursing mothers and adult women to prevent osteoporosis. When the production volume of white anchovy (Stolephorus sp) is increased, making fish flour is a preservation method, It will make the benefits of anchovy can be maximised. White anchovy flour quality can be measured by proximate characteristics and nutritional quality. Proximate parameters in this study are determination of water content, ash content, peroxide numbers, acid numbers, and saponification numbers. Nutritional quality analysis such as carbohydrates, protein, fat, calcium, iron, fiber, zinc, DHA, EPA and trans fat. The characteristics of the proximate are good and meet the quality standards of a food product from fresh anchovy (Stolephorus sp) such as fiber content, ash content, number of peroxide and trans fatty acids. The best nutritional quality of fresh anchovy (Stolephorus sp) are the content of protein, calcium, iron ,zinc, DHA and EPA.